Real-world clinical practice and outcomes in treating stage III non-small cell lung cancer: KINDLE-Asia subset - Prabhash, Kumar; Tan, Daniel Shao Weng; Soo, Ross A.; Sitthideatphaiboon, Piyada; Chen, Yuh Min; Voon, Pei Jye; Syahruddin, Elisna; Chu, Sojung; Huggenberger, Reto; Cho, Byoung-Chul (Frontiers in Oncology, 2023)
Introduction Stage III non-small cell lung cancer (NSCLC) is a heterogeneous disease requiring multimodal treatment approaches. KINDLE-Asia, as part of a real world global study, evaluated treatment patterns and associated survival outcomes in stage III NSCLC in Asia. Methods Retrospective data from 57 centers in patients with stage III NSCLC diagnosed between January 2013 and December 2017 were analyzed. Median progression free survival (mPFS) and median overall survival (mOS) estimates with two sided 95% confidence interval (CI) were determined by applying the Kaplan-Meier survival analysis. Results Of the total 1874 patients (median age: 63.0 years [24 to 92]) enrolled in the Asia subset, 74.8% were men, 54.7% had stage IIIA disease, 55.7% had adenocarcinoma, 34.3% had epidermal growth factor receptor mutations (EGFRm) and 50.3% had programmed death-ligand 1 (PD L1) expression (i.e. PD-L1 ≥1%). Of the 31 treatment approaches as initial therapy, concurrent chemoradiotherapy (CRT) was the most frequent (29.3%), followed by chemotherapy (14.8%), sequential CRT (9.5%), and radiotherapy (8.5%). Targeted therapy alone was used in 81 patients of the overall population. For the Asia cohort, the mPFS and mOS were 12.8 months (95% CI, 12.2–13.7) and 42.3 months (95% CI, 38.1–46.8), respectively. Stage IIIA disease, Eastern Cooperative Oncology Group ≤1, age ≤65 years, adenocarcinoma histology and surgery/concurrent CRT as initial therapy correlated with better mOS (p < 0.05). Conclusions The results demonstrate diverse treatment patterns and survival outcomes in the Asian region. The high prevalence of EGFRm and PD-L1 expression in stage III NSCLC in Asia suggests the need for expanding access to molecular testing for guiding treatment strategies with tyrosine kinase inhibitors and immunotherapies in this region.